2015
DOI: 10.4274/jcp.50479
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Aspect of the Society: Traditional Practices of Mother and Baby Care during Post-Partum Period and the Relevant Examples from the World

Abstract: Kültür; bir grup insan tarafından öğrenilen, paylaşılan, nesilden nesile aktarılan değerler, inançlar, tutum ve davranışlar, örf ve adetler olarak tanımlanmaktadır. İnsanların sağlıkla ilgili inanç ve uygulamaları, içinde yaşadığı toplumun kültürünün bir parçasını oluşturmaktadır. Geleneksel uygulamalar adı altında yapılan bu uygulamalar günümüzde farklı bölgelerde ve farklı kültürlerde hala kullanılmaya devam etmektedir. Gebelik, doğum ve lohusalık süreçlerindeki tıbbi uygulamaları kapsayan anne-çocuk sağlığı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
3
0
2
Order By: Relevance
“…Studies conducted in Turkey and in developing countries have also reported that traditional practices are used for diarrhoea management. In these studies, the most frequently used methods have been stated as giving oral rehydration salts (ORS) [ 5 , 21 , 26 , 29 , 33–35 ], giving a salt-sugar mixture to drink [ 5 , 24 , 26 , 29 , 33 ], continuing to provide breast milk/to breastfeed [ 21 , 22 , 33 , 34 ], increasing fluid intake [ 29 , 34 ], giving rice water to drink [ 29 , 33–35 ], giving a mix of coffee and lemon to drink [ 5 , 21 ], giving a mix of soda and aspirin [ 5 ], feeding mashed potatoes [ 5 , 22 ], feeding food made with rice [ 5 , 21 , 22 , 26 , 27 , 34 , 35 ], feeding dough [ 27 ], giving fruit juice to drink [ 27 ], feeding dry and solid foods [ 5 , 21 , 24 ], feeding soups/liquid foods [ 24 ], feeding bananas [ 5 , 22 , 34 , 35 ], feeding yogurt [ 21 , 29 ], feeding porridge [ 35 ], continuing to feed normal homemade foods [ 34 ], feeding curd cheese [ 26 ], trying to cure diarrhoea using homemade remedies [ 14 ] and various herbs [ 25 ], withholding breast milk [ 27 ], limiting fluid intake [ 24 , 29 ], and limiting food intake [ 25 ], and some results of such studies have been in line with the results of this study. It seems that there are some similarities and differences among traditional practices preferred for diarrhoea management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted in Turkey and in developing countries have also reported that traditional practices are used for diarrhoea management. In these studies, the most frequently used methods have been stated as giving oral rehydration salts (ORS) [ 5 , 21 , 26 , 29 , 33–35 ], giving a salt-sugar mixture to drink [ 5 , 24 , 26 , 29 , 33 ], continuing to provide breast milk/to breastfeed [ 21 , 22 , 33 , 34 ], increasing fluid intake [ 29 , 34 ], giving rice water to drink [ 29 , 33–35 ], giving a mix of coffee and lemon to drink [ 5 , 21 ], giving a mix of soda and aspirin [ 5 ], feeding mashed potatoes [ 5 , 22 ], feeding food made with rice [ 5 , 21 , 22 , 26 , 27 , 34 , 35 ], feeding dough [ 27 ], giving fruit juice to drink [ 27 ], feeding dry and solid foods [ 5 , 21 , 24 ], feeding soups/liquid foods [ 24 ], feeding bananas [ 5 , 22 , 34 , 35 ], feeding yogurt [ 21 , 29 ], feeding porridge [ 35 ], continuing to feed normal homemade foods [ 34 ], feeding curd cheese [ 26 ], trying to cure diarrhoea using homemade remedies [ 14 ] and various herbs [ 25 ], withholding breast milk [ 27 ], limiting fluid intake [ 24 , 29 ], and limiting food intake [ 25 ], and some results of such studies have been in line with the results of this study. It seems that there are some similarities and differences among traditional practices preferred for diarrhoea management.…”
Section: Discussionmentioning
confidence: 99%
“…The form prepared by the researchers after the literature review consisted of 25 traditional methods known to be used by mothers in Turkey when children have diarrhoea [ 5 , 11 , 12 , 21 , 22 ]. The participants were asked to choose “yes” for the methods they knew and would use when their child had diarrhoea, “no” for the ones they knew but would not use, and “I have no information on this method” for the ones they did not have any knowledge about.…”
Section: Methodsmentioning
confidence: 99%
“…28 Bilgen Sivri ve Karataş'ın yaptığı çalışmada, yenidoğan sarılığına yönelik bebeklere sarı kıyafet giydirildiği, sarı örtü/bez örtüldüğü, annenin altın taktığı saptanmıştır. 29 Türk toplumunda "lohusalık" olarak isimlendirilen postpartum dönem, Hindistan ve Tayland'ta "doing mont", Çin'de ise "zou yuezi" olarak isimlendirilmektedir. Çin, Tayland ve Hindistan'da postpartum dönemdeki kadınların ağır iş ve ev işi yapmalarına izin verilmemektedir.…”
Section: Kültürel Uygulamalarunclassified
“…Hemşirenin yaşadığı olumsuz kültürel tepkilerin engellenmesi için hizmet verdiği bireyin veya toplumun kültürel özelliklerine karşı duyarlı olmalı, saygı göstermeli, hizmet verdiği birey veya toplumun sağlık ve hastalık algıları ve tepkileri hakkında bilgi sahibi olmalı, tedavi ve bakım sürecinde holistik yaklaşımı benimsemeli, kültürün karmaşık boyutlarını anlama yeteneği kazanmalı, kültürel değerlendirme yapabilmeli, sözel olmayan iletişim yolları ile bireyin yaşadıklarını anlamaya çalışmalı, kültürel yönden uygun öğretme ve öğrenme tekniklerini kullanmalıdır. 3,7,8,[19][20][21]24,[29][30][31][32][33] Farklı kültürel değerlere sahip bireylerin sağlık ihtiyaçları da farklılık gösterebilir. Bireylerin, sONUç Küreselleşmenin sonucu olarak, dünyanın ve Türkiye'nin çok kültürlü bir yapıya dönüşmesine paralel olarak hemşirelerin farklı kültürlere sahip bireylerle karşılaşması ve bakım vermesi olası görünmektedir.…”
Section: Etkili Bakim Için Hemşirelere öNerilerunclassified
“…Customs can be learned, maintained and can be passed on to the next generation. These beliefs and practices can become a new culture for them (Sivri & Karataş, 2015).…”
mentioning
confidence: 99%